DESIGN OF MARKETING AND LOGISTICS DECISIONS OF REGARDING THE SELECTION OF MATERIALS, SPARE PARTS AND COMPONENTS - Sherepa, K. M. (Science and Transport Progress, 2007)
Contradiction is analysed between the aims of material and technical supply. The order of optimization of choice of materials, spare parts and knots is considered.